Innovative visualization practice - Baharuddin, Mohd Nasir (Universiti Putra Malaysia Press, 2015)
For any innovative visualization to be persistently practised, normally it is based from three levels of understanding and representation. These levels can be represented from macro, sub-micro and symbolic interpretations. The kinds of model that can be expressed in ‘external representations’ – that physically can be shown and available to others and ‘internal representations’, where the focus is mainly on our own cognitive process or to an individual person mind. In this case,the practice came from the process of the visualization and innovative process of judgement. Visualization, perceives the world around us symbolically, being continuous and without structure, ontologically the presentation with purpose and intended to serve, however, because of our survival and the capacity of thinking extends, it develops a new meaning about visualization and mental actions that are able to explain the natural world and its systems through a new language of sign.